Practical and theoretical implications of the new rurality in Frailesca, Chiapas, Mexico - Cadena Iñiguez Pedro; Camas Gómez Robertony; López Báez Walter; Navarro Garza, Hermilio (Revista Mexicana de Ciencias Agrícolas, 2018)
The new rurality as concept has been used in many ways, in academia some authors uses it to describe and categorize a different situation to conceive and operationalize the development towards rural population. In the political line, the new rurality has as premise that programs and actions of development favor social groups and also of beneficiaries historically benefited with the development actions. On the legal front, the new rurality emerged as an emerging concept to define and formalize decentralization of institutional activities towards the field, and the announcement of the collaboration, integration and operationalization of institutional activities with actors that from their perspective channeled actions to rural development. Hence the concept of new rurality has become popular from the recognition of the state that in rural there are not just agricultural activities developed for grown men and that not only he is the promoter of development.